2006
DOI: 10.17221/3909-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some factors on growth of lambs from crossing between the Improved Wallachian and East Friesian

Abstract: ABSTRACT:The effect of some factors (genotype, sex, litter size, age of dam at lambing, month of lambing and year of birth of lamb) on the growth of lambs -crossbreds between the Improved Wallachian (IW) and East Friesian (EF) breed was evaluated in operating conditions during two successive years. Three genotypes were evaluated: IW 50 EF 50, EF 75 IW 25 and EF 87.5 IW 12.5. The evaluation of the effect of genotype on growth showed that this factor did not have a significant effect on the majority of growth tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
4
14
1
4
Order By: Relevance
“…However, in a previous study, the effect of birth type was not significant on preweaning ADWG (26). This result was different from results of the present study and other previous studies (5)(6)(7)(8)(9). This different result may have stemmed from the genetic, maintenance, feeding, and climatic differences for Norduz sheep.…”
Section: Effect Of Environmental Factorscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in a previous study, the effect of birth type was not significant on preweaning ADWG (26). This result was different from results of the present study and other previous studies (5)(6)(7)(8)(9). This different result may have stemmed from the genetic, maintenance, feeding, and climatic differences for Norduz sheep.…”
Section: Effect Of Environmental Factorscontrasting
confidence: 99%
“…It is known that the effects of some factors, such as genotype, birth year, birth type, sex of lamb, dam's age, dam's live weight at mating season, and the maintenance and feeding of ewes, have significant influence on birth weight (BW) and weaning weight (WW) (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Litter size was the major effect influencing either survivability traits or, in particular, growth performance traits; this is in accordance with previously published studies of Gootwine and Rozov (2006), Kuchtík andDobeš (2006), andMilerski et al (2006). Wolfová et al (2009) Bucek et al (2015).…”
Section: Factors Affecting Lambs' Birth Weight Survivability and Grsupporting
confidence: 92%
“…Similar results were previously observed by Kuchtík and Dobeš (2006) (2010) also reported higher growth performance in singles compared to lambs from multiple litters. Significant differences in LW100 of twins vs. triplets (1.17 kg; P < 0.05) were observed in our study as well.…”
Section: Effect Of Litter Sizesupporting
confidence: 91%
“…Previous studies confirmed significant differences of growth performance in depending on breed (Milerski et al, 2006;Maxa et al, 2007), ewe's live weight at mating (Abdel-Mageed and El-Maaty, 2012;Aliyari et al, 2012;Vatankhah et al, 2012), litter size (Kuchtík and Dobeš, 2006;Cloete et al, 2007), sex of lambs (Mohammadi et al, 2010, Ptáček et al, 2011.…”
Section: Introductionmentioning
confidence: 77%